Divided Loyalties: A Study of a Communist-Led Trade Union’s Struggle For Survival in Trail, British Columbia, 1943-1955 - Verzuh, Ronald William (Simon Fraser University, 2017)
[E]xamines a Communist union’s struggle to survive in the post-Second World War environment of anti-Communism and anti-trade unionism that marked one of the most violent periods in the history of the Canadian labour movement. In 1943, Local 480 of the International Union of Mine, Mill and Smelter Workers in Trail, British Columbia, was nearing the end of a six-year battle for certification as the legal bargaining agent for about 4,000 smelter workers. After it achieved that goal the following year and for the next decade, it faced new battles with the employer, the powerful Consolidated Mining and Smelting Company of Canada (CM&S) with its paternalistic president S.G. Blaylock. The local also faced an array of other opponents: a workforce suspicious of a Red-tainted union with a radical past, a company union that had been established by Blaylock after the First World War, a company-loyal newspaper, and a divided community situated in the rural West Kootenay district near the Canada- United States border. Among the local’s most vigorous adversaries were the local churches, the federal government with its secret service police, and the Canadian Congress of Labour (CCL). By the 1950s, it had been purged from the CCL, shunned by the Cooperative Commonwealth Federation (CCF), and victimized by cold warriors bent on its destruction. To survive it needed to win the support of a substantially immigrant workforce with a strong alternative culture to the dominant Anglo-Saxon one. It had to address the concerns of the hundreds, perhaps thousands, of women war workers who had been hired at lower wages to replace enlisted men. And it fell into the middle of an ideological clash between the region’s two dominant left-wing political parties. Its greatest strength and potential weakness was an unabashed Stalinist named Harvey Murphy. He had been a fugitive from justice and was incarcerated in a war-time internment camp as a threat to national security, but he became an influential leader of the provincial labour movement and an outspoken advocate of workers’ rights who was hated by some and respected by others. “Divided Loyalties” begins with a victory, but Local 480’s survival for the duration of the twelve-year period of this study was far from assured.